Pengaruh Penerapan Strategi Pembelajaran Berbasis ICT Terhadap Pencapaian Hasil Belajar Sistem Komputer Siswa Kelas X SMK - Made Agustia Permata Wardani; Rufi'i; Harwanto (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2019)
This study aimed to examine the effect of ICT-based learning on learning achievement of computer system. This study was a quantitative research with quasy-experimental method and post-test only control group design model. The subject was tenth graders of a vocational high school on Multi Media and Computer Engineering and Network skill competencies as many as 90 students which was divided into two equal groups that taught using ICT-based learning and conventional method. The instrument of the study was a written test (post-test) to measure the learning achievement. The data was analyzed by independent-samples T Test at 0.05 significance level. The finding revealed that coefficient t-test (10.025) > ttable (1.987) with p-value (2-tailed) 0.000, so there was a significant difference on computer system’s learning achievement between groups that taught using ICT-based learning and conventional methods. Thus, ICT-based learning has a significant effect on the students’ learning achievement of computer system.